(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
Sustainable supply chain management (SSCM) has appeared to be important in business practices in order to survive in the competition. Sustainable performance assessment, that includes economic, social, and environmental aspects need to be given due attention by the business players in order to understand the position of the company so that it can fulfill customer satisfaction. In this research, each of the aspects is measured using different methods. The Economic performance assessment is represented using the Supply Chain Operation Reference (SCOR) model that helps in measuring the success of a supply chain operation. It uses 15 indicators deemed relevant in the Make-to-Stock production typology that is distributed into five performance attributes. The economic assessment is then obtained through these performance attributes that result in 97.5% in agility, 92% in cost, 78.2% in reliability, 72% in asset management, and 40.67% in responsiveness. Meanwhile, the social performance assessment is directed at employee's welfare. Questionnaires are distributed to 30 employees to measure company's commitment to address their social issues. It results in a perfect score as 100% in fair salary, annual allowance, and training, while health insurance and safety equipment only cover 70% and 30%, respectively. The environmental aspect is noticed on the wastewater management, since it mainly contributes for company's waste. The assessment lies on the liquid contamination test and is compared to the maximum standard level, set by the government. Environmental assessment shows 76.8% in acidity, 71.93% in Biological Oxygen Demand (BOD), 33.15% in temperature, and 0% in both Total Suspended Solid (TSS) and Chemical Oxygen Demand (COD). While this research is focusing on improving the performance in the supply chain process (Economic aspect), which is the worst assessment in the economic aspect, which is responsiveness, it is selected to be improved to reach an optimum performance. Therefore, the operation-overlapping approach is applied in the scheduling of the production process to improve company’s responsiveness, which is from 40.67% to 60.67%.